MODEL SISTEM DINAMIS PERENCANAAN BAHAN BAKU PADA PRODUK VENEER DI PT. XYZ - Bambang Herry Purnomo; Aqidatul Izza (AGROINTEK, 2020)
PT. XYZ is a company that processes raw materials in the form of wood into veneers, which are semi-finished products from plywood. The veneer production process at PT. XYZ is currently experiencing stockout of raw materials, so the company has not been able to meet the number of consumer requests. The company has also experienced an increase in raw material inventory, this is due to the delay in the response of raw materials to be produced. Based on this, raw material planning is needed to minimize the occurrence of stockouts and increase inventory, so that when viewed from quantity, quality and timings are more optimal. Data needed to design dynamic system models are past demand data, raw material inventory, production capacity, and production warehouse capacity, which are designed using powersim studio 2005 software. Based on the raw material planning scenario, the optimistic scenario is the best scenario to minimize inventory amounting to 643,092 m3 / month from the total log face and log core, and also can reduce the average stockout of the total log face and log core by 887,561 m3 / month. The changed parameters are by increasing the safety stock by 10%, and accelerating the response of information from 30 days to 7 days.